DETERMINATION OF PESTICIDE RESIDUES IN BRINJAL FRUIT AT SUPERVISED TRIAL - M. F. Iqbal; U. Maqbool; M. R. Asi; S. Aslam (Journal of Animal and Plant Sciences, 2007)
Supervised field trial of brinjal was conducted during May, 2006 to determine Chlorpyriphos, Acephate, Dichlorovos, Carbofuran and Imidachloprid residues by adopting HPTLC method. These insecticides were sprayed directly on the brinjal crop and data were recorded after 0, 3 and 7th day after application. The samples were treated with organic solvent ethyl acetate and cleaned-up by activated charcoal. All the samples were found contaminated with pesticide residues except Imidachloprid. After 0 day the quantity of pesticide residues was maximum followed by 3rd day that contained lesser amount of insecticide residue and after 7th day the quantity of these residues were negligible in the brinjal fruit which led to conclusion, that the brinjal fruit was suitable for the consumption of public after three days with out posing any hazard to human health.
Keywords: Pesticides; residues; brinjal fruit; HPTLC